The Effectiveness of Career Information Service with Mind Mapping Technique to Improve Students Occupational Knowledge (Universitas Negeri Semarang, 2018)
This research aims to improve students' career understanding through career information service with Mind Mapping technique. The experimental method used pre-test post-test control group design, involving 2 classes as control group and experimental group. The results of this study indicate that students who obtain career information services with mind mapping techniques have increased understanding of career higher than students who do not get information carier information with mind mapping techniques.